Analysis and solution of 'A' Pillar blind spots in cars - Boo, Jun Kang (2018)
Modern vehicle manufacturers have been trying to create the ultimate design to incorporate aesthetics, performance and safety for decades. With an ever growing car population, the rate of road accidents has also been on the rise. Some of these accidents could have been avoided should the driver had a clear vision of his surroundings at the time.